The earliest research of tending felling established according to IUFRO system in north-west of Russia. Issue 1 (October 2021) - Belyaeva, N; Danilov, D; Kuznetsov, E
Abstract: Research facilities on thinning operations for forests in North-West of Russia were established during 1929-1930 according to technique accepted by the II World Forestry Congress in 1928 in Rome. The purpose of this work originally consist on clarification of effectiveness of this forestry measures, degree of its influence on an increase for growing stock, height, and on quality of timber. This necessity was caused by the fact that it was the first such experience at that time. The main objective consisted in specification of intensity and techniques of thinning. There are structural changes in elevated and underground plants biomass in a stand. On all research facilities the appearance of spruce-tree advance growth is noted. The thinning can affect on the course of natural reforestation and does not cause fundamental change in the ratio between a grass and moss layers. They shift this ratio in favor of the first one and it allows claiming about the possibility of bio-circulation intensity increase by means of regular tending felling of the forest. Now it is the most valuable research facility allowing coming to scientifically substantiated conclusion about techniques of thinning which correspond to exact combination the silvicultural and economic requirements for forest management.